1985
DOI: 10.1002/ajpa.1330680206
|View full text |Cite
|
Sign up to set email alerts
|

Cemental annulation enhancement: A technique for age determination in man

Abstract: Cemental annulations are easily countable in teeth from animals that have an exaggerated regular change of food intake from season to season. Although present in human teeth, cemental annulations are not always easy to count. A method for preparing human teeth for evaluation involving collection, identification, measuring, sectioning, cleaning, acid etching, staining, and mounting is reported. Sections 100-microns thick were stained with cresyl fast violet as a stain of choice and were photographed using stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
7

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 4 publications
0
25
0
7
Order By: Relevance
“…Further technical improvements led to the suggestion that the TCA was superior to other tooth-based methods of age estimation in the adult skeleton [19]. Initially, the TCA method was applied to freshly extracted teeth, but Grosskopf, in 1989, showed that this method was also applicable to historical skeletons and cremations [20].…”
Section: Discussionmentioning
confidence: 99%
“…Further technical improvements led to the suggestion that the TCA was superior to other tooth-based methods of age estimation in the adult skeleton [19]. Initially, the TCA method was applied to freshly extracted teeth, but Grosskopf, in 1989, showed that this method was also applicable to historical skeletons and cremations [20].…”
Section: Discussionmentioning
confidence: 99%
“…Countability of annulations from photographic enlargements was evaluated. However, it is not always easy to count [115]. Miller et al [116] reported that determining chronologic age in humans from cementum annulations is not possible.…”
Section: Histological Methodsmentioning
confidence: 99%
“…25,26 Cemental annulations are not always easy to count. Mineralized 100µ thick cross-sections were subjected to one of the three treatments: unstained, stained with Villanueva's blood stain and stained with acridine orange.…”
Section: Cementum In Age Determinationmentioning
confidence: 99%
“…Mineralized 100µ thick cross-sections were subjected to one of the three treatments: unstained, stained with Villanueva's blood stain and stained with acridine orange. 26,27 Cresyl fast violet, Toluidine blue, hematoxylin or periodic acid Schiff (PAS) can also be used for staining. Ideal areas were selected by light microscopy and photographed.…”
Section: Cementum In Age Determinationmentioning
confidence: 99%